Hepatic Resection Versus Transarterial Chemoembolization for Intermediate-Stage Hepatocellular Carcinoma: A Cohort Study - Lu, Linbin; Zheng, Peichan; Wu, Zhixian; Chen, Xiong (Frontiers in Oncology, 2021)
Background The selection criteria for hepatic resection (HR) in intermediate-stage (IM) hepatocellular carcinoma (HCC) are still controversial. We used real-world data to evaluate the overall survival (OS) in treatment with HR or transarterial chemoembolization (TACE). Methods In total, 942 patients with IM-HCC were categorized into the HR group and the TACE group. OS was analyzed using the Kaplan–Meier method, log-rank test, Cox proportional hazards models, and propensity score-matched (PSM) analysis. Curve smoothing was performed through the generalized additive model. The interaction test was performed to evaluate the impact of HR on OS concerning risk factors. Also, we used multiple imputation to deal with missing data. Results In total, 23.0% (n = 225) of patients received HR. At a median OS of 23.7 months, HR was associated with improved OS in the multivariate analysis [hazard ratio (HzR) = 0.45, 95%CI = 0.35–0.58; after PSM: HzR = 0.56, 95%CI = 0.41–0.77]. Landmark analyses limited to long-term survivors of ≥6 months, ≥1 year, and ≥2 years demonstrated better OS with HR in all subsets (all p < 0.05). After PSM analysis, however, HR increased the risk of death by 20% (HzR = 1.20, 95%CI = 0.67–2.15) in the subgroup of patients with lactate dehydrogenase (LDH) ≤192 U/L (p for interaction = 0.037). Furthermore, the significant interaction was robust between the LDH and HR with respect to the 1-, 3-, and 5-year observed survival rates (all p < 0.05). Conclusion HR was superior to TACE for intermediate-stage HCC in patients with LDH levels >192 U/L. Moreover, TACE might be suitable for patients with LDH levels ≤192 U/L.